The Complete Codes and Statutes if the State of Montana In Forcce July 1, 1895, pg. 1084, pt. 1, tit. 11, § 758 - (:unkn) unknown (General Publisher, 1895)
Every person who within the limits of any city or town carries or bears concealed about his person a dirk, dagger, pistol, revolver, or other deadly weapon is punishable by a fine not exceeding one hundred dollars. This Section does not apply to peace officers in discharge of their official duty.
--
Keywords: CARRY - CONCEALED